Study on Application of Diacetylene- containing Copolyurethanes (DA-coPUs) coating as strain sensors using Raman Spectroscopy - Sutrisno, Widayani; Stanford, John L.; Lovell, Peter A. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2005)
A two-phase copolymer DA-coPUs containing of 50% hard-segment has been prepared using a polyoxypropylene-diol with molecular weight of 2000 (Voranol 2000), 4,4 -diphenylmethane diisocyanate(MDI) and 2,4-hexadiyne-1,6-diol (HDD) via a one-shot, bulk polymerization process. Solution of linear, as-prepared DA-coPUs in N,N-Dimethylacetamide (DMAc) was coated onto pre-heated steel beam. Cross polymerization of the DA-coPUs were carried out using heating under nitrogen at 100â—¦C for 5 hours. Deformation micromechanics of the DA-coPUs has been studied using simultaneous 4-point bending testing and Raman spectroscopy. The results showed that the coating has poorer strain- induced Raman band shift factors than that of pure DA-coPUs [1]